ASSESSMENT OF LEVELS, DISTRIBUTION, AND ECOLOGICAL RISKS OF POLYCYCLIC AROMATIC HYDROCARBONS FROM SELECTED WASTE DUMPSITES - Schneider, Julia; O'Reilly , Liam; Al-Mansoori, Fatima (Ayden International Journal of Basic and Applied Sciences, 2024)
This study investigates the levels, distribution and ecological risk of polycyclic aromatic hydrocarbons (PAHs) in surface soils of some selected wastes dumpsites in Bayelsa State, Nigeria. Polycyclic aromatic hydrocarbons (PAHs) are petty pollutants frequently seen in quite a lot of vicinity that threaten the populace living in close proximity to them. True representative samples of the study and control areas were collected and analyzed for PAHs using Gas Chromatography– Mass Spectrometer (GC–MS). The analyzed PAHs concentrations varies from 40.256 mg/kg for Swali, 10.63549 mg/kg for Opolo, 60.91517 mg/kg for Tombia Round About, and 19.3009 mg/kg for Igbogene wastes dumpsites respectively. Moreover, the total PAHs concentrations in a given station were seen to be higher than the Dutch guideline maximum limits of 40 mg/kg although not for an individual PAHs. The obtained results equally showed the first and second highest single concentration of PAHs composite detected at an individual site for indeno [1,2,3-cd]pyrene (IcdP) to be 22.55850 mg/kg and 8.784 mg/kg for fluoranthene at Tombia round about, this astronomic rise maybe due to its commercial nerve midpoint in Yenagoa Metropolis